CHUKWUMA ANYANWU: DRAMATIC REFLECTIONS ON THE NIGERIAN SOCIETY - Imiti, Aghogho Lucky (International Review of Humanities Studies, 2021)
Drama performs various roles in the society. One of such roles is the re-presentation of past events. These past events are historical antecedents which a given society is meant to be abreast of in order to cut a proper walking path for the future, either to avoid pitfalls of the past or uphold a certain standard. Likening drama to a mirror, this paper discussed the reflective nature of drama in the Nigerian society. Through the use of the literary method, Chukwuma Anyanwu’s dramatic texts, Stunted Growth, The Battle, Another Weekend, Gone! and Broken Image, were analysed to ascertain how well the playwright was able to project the Nigerian society through these works. It was discovered that the plays were well crafted by the author and that they mirrored the Nigerian milieu. It was therefore concluded that members of the society, especially the political class, should learn from these plays and build a society that is devoid of intimidation, corruption, oppression of the masses and the mass media, in order for democracy to thrive.